ANALYSIS OF COMMUNITY PERCEPTIONS TOWARDS THE EXISTENCE OF SATRIA BUS MASS TRANSPORTATION IN KEDIRI CITY - Pertiwi , Ananda Tria Budi; Widiyanto, Wahyu (MSJ : Majority Science Journal, 2024)
This research aims to determine public perceptions regarding free city transportation "Satria Bus" in Kediri City, as well as finding out the advantages and disadvantages of this city transportation. The method in this research is descriptive with a qualitative approach using observation, interview and documentation study techniques. The validity test used is source triangulation. From the research results, it is known that the public's perception of the Satria Bus is that they are greatly helped by the free facilities provided by the Kediri City government. Satria buses can reduce the number of traffic accidents and reduce people's use of private vehicles which has an impact on reducing congestion. The existence of free buses is very supportive, especially for people in Kediri City as a means of moving from one place to another to carry out activities. This shows that the Satria Bus is very useful for the people in Kediri City. So, the government takes better care of the maintenance of the Satria Bus.